Small pulmonary granuloma is often misdiagnosed as lung cancer by positron emission tomography/computer tomography in diabetic patients. (27th August 2018) - Lu, Tao; Zhan, Cheng; Huang, Yiwei; Zhao, Mengnan; Yang, Xiaodong; Ge, Di; Shi, Yu; Wang, Qun
Abstract: OBJECTIVES: A small pulmonary granuloma (SPG) is often misdiagnosed as lung cancer in diabetic patients by positron emission tomography/computed tomography (PET/CT). The present study was conducted to investigate whether diabetes is the influencing factor and to determine other related factors that have an impact on the diagnostic results following PET/CT examination. METHODS: All clinical, imaging and pathological data of patients diagnosed with pulmonary nodules by PET/CT from January 2004 to December 2017 in our department were collected. Patients with an SPG who were wrongly diagnosed with lung cancer by PET/CT were enrolled ( n  = 79). The propensity score matching method was used to create a comparable control adenocarcinoma group ( n  = 395). Maximum standard uptake values, diabetes and fasting blood–glucose (FBG) were determined and analysed. RESULTS: The average maximum standard uptake values in the 2 groups were comparable ( P  = 0.801). Maximum standard uptake values in 5 subsections were not significantly different between the 2 groups ( P  = 0.135). The odds ratio (OR) of 3.326 [95% confidence interval (CI) 1.671–6.623] for diabetes favoured misdiagnosis and was statistically significant ( P  < 0.001). Furthermore, in patients with high FBG levels (≥7.0 mmol/l), the risk of misdiagnosis of SPG increased significantly compared with normal FBG level (OR 2.601, 95% CI 1.174–5.761; P  =   0.015). CONCLUSIONS: Diabetes and high FBG level were the influencing factors in the false-positive results of lung cancer by PET/CT examination.